Diversity Of Types And Abundance Of Algae, In Meras Waters Of North Sulawesi, Photosynthesis Pigments And Cell Structure - Kumampung, Deislie Roxmerie H; Lumoindong, Frans; Angkouw, Ester Dellayani (Sam Ratulangi University, 2024)
Research on the diversity of algae types and their abundance in Meras waters has been carried out using structured line transect sampling and quadrant placement methods. The result is a diversity of algae types with a Shannon index (H') above 1.75. This shows that the diversity of algae types is moderate where water conditions are still good enough for algae growth. This is reinforced by the results of analysis of the structure of algal cells using TEM which found the presence of Floridian starch as evidence of the photosynthesis process taking place in these waters. When algae to grow and develop will carry out the process of photosynthesis. There were 9 species of algae found spread across 3 classes, namely 3 species of Chlorophyceae, 4 species of Phaeophyceae, and 3 species of Rhodophyceae. The results of the analysis of species abundance in these waters show that the algae species Gracilaria edulis is the most abundant, namely 7.6 individuals/m2, while the relative abundance is 0.28. The results of the analysis of photosynthetic pigments in the algae Gracilaria edulis were chlorophyll a, namely 359.335 µg, chlorophyll d 47.385 µg, and 1627.75 µg of carotene pigment. This algae pigment can be used as a raw material in the food (nutrification) and pharmaceutical industries. Keywords: Diversity of algae types, pigments, and cell structure Abstrak Penelitian Keanekaragaman jenis alga dan kelimpahannya di perairan Meras telah dilakukan dengan metode pengambilan sampel line transek dan peletakan kuadran secara terstruktur. Hasilnya adalah keanekaragaman jenis alga dengan index Shannon (H’) berada di atas 1,75 Hal ini menunjukkan bahwa keanekaragaman jenis alga sedang dimana kondisi perairan masih cukup baik untuk pertumbuhan alga. Hal ini diperkuat dengan hasil analisis struktur sel alga menggunakan TEM ditemukan adanya floridean starch bukti adanya berlangsung proses fotosintesis di perairan tersebut. Dimana alga untuk tumbuh dan berkembang akan melakukan proses fotosintesis. Spesies alga yang ditemukan sebanyak 9 spesies yang tersebar dalam 3 kelas yaitu Chlorophyceae 3 spesies, Phaeophyceae 4 spesies dan 3 spesies Rhodophyceae. Hasil analisis kelimpahan spesies di perairan tersebut menunjukkan bahwa spesies alga Gracilaria edulis paling melimpah yaitu 7,6 individu/m2 sedangkan kelimpahan relatifnya adalah 0,28. Hasil analisis pigmen fotosintesis pada alga Gracilaria edulis adalah klorofil a yaitu 359,335 µg, klorofil d 47,385 µg dan 1627,75 µg pigmen karoten. Pigmen alga ini dapat dimanfaatkan sebagai bahan baku dalam industri makanan (nutrifikasi) dan farmasetika. Kata kunci : Keanekaragaman jenis alga, pigmen, dan struktur sel.